Performance study on a membrane absorber-evaporator component of a solar-driven membrane-based absorption heat pump (MAHP) - Low, Elaine (2024)
The membrane-based absorption heat pump (MAHP) is a compact-sized, thermally-driven absorption refrigeration system (ARS) that recovers low-temperature renewable or waste heat from a refrigerant stream. MAHP can be used for absorption heating, cooling, or desiccant dehumidification applications operating at a smaller scale. As the solution film thickness in the existing falling film absorbers is inconsistent during operation, using membrane modules can help to mechanically constrain the solution film by forming membrane microchannels with consistent thickness. Besides, the use of membranes also significantly increases the membrane-fluid interfacial area, which is conducive to improving heat and mass transfer performance.